Persepsi Mahasiswa FKM Unmuha Terhadap Kawasan Tanpa Rokok (KTR) Di Lingkungan Kampus Universitas Muhammadiyah Aceh Tahun 2022 - M. Mirad Alfayrazi, Eddy Azwar, Asnawi Abdullah (CV. PUSDIKRA MITRA JAYA, 2022)
Tobacco users will kill >3 million deaths/year worldwide. This figure will continue to increase to 8 million deaths/year by 2030. Aceh province is one of the other provinces with the highest prevalence of smokers in Indonesia. The proportion of smokers in Aceh province is 29.3% and active smokers reach 25.0%, non-smokers 68.2%, occasional smokers 4.3%, and ex-smokers 2.5%. The purpose of this study was to determine the relationship between knowledge and attitudes with students' perceptions of FKM UNMUHA towards a smoke-free area (KTR). This research is descriptive analytic with cross sectional design. The population in this study were all regular students of UNMUHA Class of 2017-2020 with a total of 154. The sample used in this study was 61 students. Purposive sampling where the researcher determines the sample by determining the special characteristics according to the criteria of the sample. The results showed that there was a relationship between attitudes (p value = 0.025) and UNMUHA students' perceptions of KTR. Meanwhile, knowledge does not have a relationship with UNMUHA students' perceptions of KTR in the Muhammadiyah Aceh University campus environment (p value = 0.945).